Manajemen Branding Anwaha : Penelitian - Syahrani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Anwaha, as a formal educational institution based on pesantren with three levels of education, namely MI Tahfidz Anwarul Hasaniyyah, MTs Anwarul Hasaniyyah, and MA Anwarul Hasaniyyah, is building a brand to facilitate students, who are the target market for Anwaha's education. In Anwaha's branding management, several steps are taken, including proving its excellence in science and religious fields, providing the best facilities, online and offline promotions, as well as certification programs for educators and educational staff.